Helium 4 - Galasiewicz, Zygmunt M. (Commonwealth and international library. Selected readings in physics., 1971)
Helium 4 is a collection of materials that examines the various properties of helium 4. The book presents 12 experimental studies and seven theoretical studies. The coverage of the text includes the viscosity of liquid helium below the?-point; the transfer of helium II on glass; and the determination of the velocity of propagation of the second sound in helium II. The theoretical papers tackle topics such as the theory of superfluidity of helium II; radiation of sound in helium II; and the kinetic coefficients of helium II. The book will be of great interest to chemists, chemical engineers, a.